Experimental Investigation of Thermal Response of Encased Composite Beams - R. Abid, Sallal; I. Mussa, Faten; TayÅŸi, Nildem (International Journal of Engineering and Technology, 2018)
Many types of structures, or part of which, are directly under the exposure of the time-dependent variations of the temperature of air and solar radiation. Such thermal loads can vary the temperature of the different parts of the structural members causing undesired structural effects. In this research, an experimental study was conducted to investigate the influence of such thermal loads on composite beams. For this purpose, a concrete-encased-steel beam was instrumented with fifteen thermocouples and other sensors. The records were captured for a sunny winter day with moderately high daily air temperature difference of more than 18 oC and a solar radiation of more than 700 W/m2. The results showed that the hourly temperature variation and the sun movement in addition to the altitude angle of sun rays control the vertical and lateral temperature distributions of the beam. The maximum recorded difference between hourly maximum and minimum temperatures of the beam was 12.5 oC.Â Â